Castles in Townscapes: Studying Fortified Medieval Towns and their Environments in Eure-et-Loir (France). (3rd July 2019) - Borderie, Quentin; Acheré, Vincent; Lecroère, Thomas; Labat, Olivier; Capron, François; Pinhède, Anaïs; Louis, Antoine; Douard, Michel
ABSTRACT: In the north of France, fortified towns and their castles have made a strong environmental impact since the eleventh century or earlier. This paper describes recent research that has begun to analyse the environmental impact of fortified towns during the medieval period, specifically between the eighth and the sixteenth centuries. The focus is on the place of fortifications within the townscape and the link between town and country, particularly through various forms of artificialisation – human modification – of the hydrological system. The case study area south-west of Paris, containing 33 medieval defended towns, was the location of conflicts on the borders of the French royal domain during this period. In many towns, defensive walls and moats can still be seen, and good preservation of the town plan and limited urban development since the nineteenth century has enabled environmental data to be obtained from ditches and rivers, while historical maps, excavations and archival studies, supported by some geophysical survey, has facilitated more detailed analyses.